Pengaruh Work-Life Balance Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Kebayoran Lama Kota Jakarta Selatan - Retno Japanis Permatasari (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of work-life balance and work motivation on employee performance at the Kebayoran Lama District Office, South Jakarta. The underlying phenomenon of this study is the emergence of continuity between employees' personal and work lives, which has an impact on decreasing work enthusiasm and productivity. This study used a quantitative approach with a survey method of 50 respondents selected through a purposive sampling technique. Data were collected using a Likert-sized questionnaire and analyzed using multiple linear regression with the help of SPSS. The results showed that work-life balance had a positive and significant effect on employee performance, while work motivation also had a positive influence on performance improvement. Simultaneously, both variables had a strong contribution to employee performance with a coefficient of determination of 0.68 or 68%. These findings indicate that work-life balance, as well as motivational drive, are key factors in building ASN productivity in the government environment.